Racial bias in neural response to others' pain is reduced with other-race contact. (September 2015) - Cao, Yuan; Contreras-Huerta, Luis Sebastian; McFadyen, Jessica; Cunnington, Ross
Abstract: Observing the pain of others has been shown to elicit greater activation in sensory and emotional areas of the brain suggested to represent a neural marker of empathy. This modulation of brain responses to others' pain is dependent on the race of the observed person, such that observing own-race people in pain is associated with greater activity in the anterior cingulate and bilateral insula cortices compared to other-race people. Importantly, it is not known how this racial bias to pain in other-race individuals might change over time in new immigrants or might depend on the level and quality of contact with people of the other-race. We investigated these issues by recruiting Chinese students who had first arrived in Australia within the past 6 months to 5 years and assessing their level of contact with other races across different social contexts using comprehensive rating scales. During fMRI, participants observed videos of own-race/other-race individuals, as well as own-group/other-group individuals, receiving painful or non-painful touch. The typical racial bias in neural responses to observed pain was evident, whereby activation in the anterior cingulate cortex (ACC) was greater for pain in own-race compared to other-race people. Crucially, activation in the anterior cingulate to pain in other races increased significantly with the level of contact participants reported with people of the other race. Importantly, this correlation did not depend on the closeness of contact or personal relationships, but simply on the overall level of experience with people of the other race in their every-day environment. Racial bias in neural responses to others' pain, as a neural marker of empathy, therefore changes with experience in new immigrants at least within 5 years of arrival in the new society and, crucially, depends on the level of contact with people of the other race in every-day life contexts.